Hallowe'en Party - Christie, Agatha (London HarperCollins Publishers, 1994)
Mystery writer Ariadne Oliver has been invited to Woodleigh Common, where a Hallowe'en party is under way for a group of local adolescents, one of whom is a young girl known for telling tall tales of murder and intrigue. When the girl falls victim to a tart game of apple bobbing gone wrong, Ariadne wonders just how tall her latest tale was. Which of the party guests wanted to keep her quiet is a question for her partner in crime, Hercule Poirot. But unmasking a killer this Hallowe'en isn't giong to be easy, for there isn't a soul in Woodleigh who believes the late little storyteller was even murdered.
English Fiction.
Keywords: Poirot, Hercule (Fictitious character) -- Private investigators -- England